OER Quality and Adaptation in K-12: Comparing Teacher Evaluations of Copyright-Restricted, Open, and Open/Adapted Textbooks - Kimmons, Royce (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
Conducted in conjunction with an institute on open textbook adaptation, this study compares textbook evaluations from practicing K-12 classroom teachers (n = 30) on three different types of textbooks utilized in their contexts: copyright-restricted, open, and open/adapted. Copyright-restricted textbooks consisted of those textbooks already in use by the teachers in their classrooms prior to the institute, open textbooks included alternatives from CK-12 and OpenStax, and open/adapted consisted of open textbooks that the teachers devoted time to adapting to their individual needs. Results indicate that open/adapted textbooks were evaluated as having the highest quality, and that open textbooks were of higher quality than copyright-restricted textbooks. Though some factors of quality might be influenced by cost differences (e.g., timeliness and the ability to adopt updated textbooks), results reveal that open and open/adapted textbooks may do a better job of meeting the needs of K-12 teachers in a variety of ways that may not be captured through traditional approaches to quality assurance. This study marks an early step in exploring the quality of K-12 open educational resources (OER) and the use of practicing teachers as authentic evaluators of textbooks for their local contexts.